2013
DOI: 10.1115/1.4024394
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flow Stress for Commercially Pure Titanium Subjected to Electrically Assisted Deformation

Abstract: Uniaxial tension tests were conducted on thin commercially pure (CP) titanium sheets subjected to electrically assisted deformation using a new experimental setup to decouple thermal–mechanical and possible electroplastic behavior. The observed absence of stress reductions for specimens air-cooled to near room temperature motivated the need to reevaluate the role of temperature on modeling the plastic behavior of metals subjected to electrically assisted deformation, an item that is often overlooked when invok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(57 citation statements)
references
References 26 publications
2
55
0
Order By: Relevance
“…They also found that the threshold energy decreases with Zn addition. Magargee et al, in a recent publication [19] presented an interesting result where commercially pure thin titanium sheets were subjected to electric currents at near isothermal condition by external cooling. The usually observed stress drops were not present and fundamental questions on the role of electric current in such experiments were raised.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…They also found that the threshold energy decreases with Zn addition. Magargee et al, in a recent publication [19] presented an interesting result where commercially pure thin titanium sheets were subjected to electric currents at near isothermal condition by external cooling. The usually observed stress drops were not present and fundamental questions on the role of electric current in such experiments were raised.…”
Section: Introductionmentioning
confidence: 96%
“…[9,10] The interest in electroplasticity has gained much interest of late [11][12][13][14][15][16] in the potential application of enhancing formability [7] and reducing spring-back [17] in sheet metal components. The application is especially useful in materials such as magnesium, [18] titanium, [19] and certain aluminum alloys, [15] which exhibit poor formability at room temperature. The warm forming which is generally required for such alloys can be replaced by electrically assisted forming.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature profiles in Fig. 2 shows that temperature distributions during the tests were quite uniform along the gage length in comparison with those of titanium [18] tested under a continuous electric current with low electric current density. Pulsing strain of 1.5% Figure 3.…”
Section: Resultsmentioning
confidence: 97%